A new comb-star (Asteroidea, Astropectinidae) from the Upper Triassic (Carnian) of China - Gale, Andrew S. (Zootaxa, 2020)
A new astropectinid asteroid, Eoastropecten sechuanensis gen. et sp. nov. is described from the Upper Triassic (Carnian) of Sechuan Province, China, based upon marginal ossicles. This occurrence extends the known fossil record of the family Astropectinidae back by 50 myr from the Lower Jurassic, and indicates that a significant part of the radiation of the neoasteroids probably took place around 240 Ma, only 12 myr after the P–T boundary extinction.